1999
DOI: 10.1520/jfs14601j
|View full text |Cite
|
Sign up to set email alerts
|

Population Data on the Thirteen CODIS Core Short Tandem Repeat Loci in African Americans, U.S. Caucasians, Hispanics, Bahamians, Jamaicans, and Trinidadians

Abstract: Allele distributions for 13 tetrameric short tandem repeat (STR) loci, CSF1PO, FGA, TH01, TPOX, VWA, D3S1358, D5S818, D7S820, D8S1179, D13S317, D16S539, D18S51, and D21S11, were determined in African American, United States Caucasian, Hispanic, Bahamian, Jamaican, and Trinidadian sample populations. There was little evidence for departures from Hardy-Weinberg expectations (HWE) in any of the populations. Based on the exact test, the loci that departed significantly from HWE are: D21S11 (p = 0.010, Bahamians); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(108 citation statements)
references
References 15 publications
4
94
0
8
Order By: Relevance
“…The standardization of accurate microsatellite genotyping systems that can be used in different laboratories and the effective use of the generated molecular profiles as descriptors for a particular crop of interest require validation steps to confirm that the same molecular patterns are obtained at different institutions. For instance, the establishment of a typing system in humans for forensic purposes was the result of an organized validation effort involving a number of laboratories worldwide (Kimpton et al, 1996), which yielded a set of 13 internationally recommended SSRs (Budowle et al, 1999). A similar study conducted for Eucalyptus involving an international network of laboratories in eight countries resulted in a set of 25 SSRs for the characterization of this genus, with six loci P.C.B.…”
Section: Discussionmentioning
confidence: 99%
“…The standardization of accurate microsatellite genotyping systems that can be used in different laboratories and the effective use of the generated molecular profiles as descriptors for a particular crop of interest require validation steps to confirm that the same molecular patterns are obtained at different institutions. For instance, the establishment of a typing system in humans for forensic purposes was the result of an organized validation effort involving a number of laboratories worldwide (Kimpton et al, 1996), which yielded a set of 13 internationally recommended SSRs (Budowle et al, 1999). A similar study conducted for Eucalyptus involving an international network of laboratories in eight countries resulted in a set of 25 SSRs for the characterization of this genus, with six loci P.C.B.…”
Section: Discussionmentioning
confidence: 99%
“…Finally allele 7 of D13S317, which appears in one individual from Santiago Is. (CVS), has only been spotted in Bahamians and Jamaicans (Budowle et al 1999). Results from the admixture analysis show an extremely high percentage of the p 1 contribution to the Cabo Verde gene pool (Table 3).…”
Section: Allele Comparisonsmentioning
confidence: 99%
“…Further, two Chinese populations revealed that a relatively small number of loci were different from Koreans: a Shanghai population differed at 6 loci (Li et al, 2009) and a Yunnan Han China population at 4 loci (Nie et al, 2008). Although, a Southwestern American Hispanic population showed significant differences at only 5 loci (Budowle et al, 1999), the R st values indicated that two Chinese populations are more close to Korean population than American Hispanic population (R st value: Shanghai, 0.00301; Yunnan-Han, 0.00147; US Hispanic, 0.02589).…”
Section: Population Genetic Data Of 15 Autosomal Strsmentioning
confidence: 96%
“…Allele frequencies of most loci in the Korean population were significantly different from those in European or American populations (p < 0.05). For example, by comparisons of a Korean population, Greek (Sánchez-Diz et al, 2008) and Brazilian populations differed at 12 loci (Fridman et al, 2008), while US Caucasian and African-American populations differed at 11 STR loci (Budowle et al, 1999). Further, two Chinese populations revealed that a relatively small number of loci were different from Koreans: a Shanghai population differed at 6 loci (Li et al, 2009) and a Yunnan Han China population at 4 loci (Nie et al, 2008).…”
Section: Population Genetic Data Of 15 Autosomal Strsmentioning
confidence: 99%